Short communication: Savanna-forest boundary on Mount Rinjani, Lombok Island, West Nusa Tenggara, Indonesia - Sutomo SUTOMO; Eddie van Etten; Rajif Iryadi (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Sutomo, van Etten E, Iryadi R. 2021. Short communication: Savanna-forest boundary on Mount Rinjani, Lombok Island, West Nusa Tenggara, Indonesia. Biodiversitas 22: 726-731. Seasonally dry tropical forests tend to be bordered by or are mixed with savanna ecosystems. This research investigates the location and nature of forest-savanna boundary on Mt. Rinjani and hypothesizes on potential causes of such boundary formation. The field survey locations were based on MODIS burnt area data. We made 30 plots (50 x 50 m) established along transects to obtain vegetation and environment data across boundaries. For data analysis, we use community correspondence index (CCI), vegetation composition using Importance Value Index (IVI), and Analysis of Similarity (ANOSIM) to detect differences in floristic and environmental characteristics across boundaries. Species composition in the transition zone (based on highest IVI results) comprises Ficus septica, Macaranga tanarius, Lindera sp., Engelhardia spicata, Saurauria sp., Rytidosperma penicillatum, and Athyrium sp. The Non-Metric Multi-Dimensional Scaling (NMDS) based on environmental data showed clear separation between savanna and forest, although boundaries were floristically similar to forest. Micro- and macro-environmental factors, as well as, fire disturbances, are also important features of the forest-savanna boundary on Mt. Rinjani. We present evidence of boundary dynamics in the form of forest advance on the Mt. Rinjani south-west slope.